Pengaruh Fosfor Dan Zeolit Terhadap Pertumbuhan Dan Hasil Sawi Pagoda (Brassica narinosa L.) - Panunggul, Victor Bintang; Nurbaiti, Idhata (Universitas Wiralodra, 2025)
The use of phosphorus and zeolite can be an option to improve soil fertility and nutrients for pagoda mustard plants. This study aims to determine the effect of phosphorus and zeolite on the growth and yield of pagoda mustard. This study used a factorial completely randomised design with three replications. The first factor is phosphorus, consisting of three levels: F0 (control), F1 (60 g/polybag), and F2 (100 g/polybag). The second factor is zeolite fertiliser, consisting of three levels: L0 (control), L1 (50 g/polybag), and L2 (90 g/polybag). The two factors resulted in nine treatment combinations. The combination of the two factors totalled nine treatments, which were then repeated three times, resulting in 27 experimental units. The observation variables were plant height, number of leaves, plant fresh weight, root fresh weight and root length. The results showed that there was no interaction between phosphorus and zeolite application on the growth and yield of pagoda mustard plants. The addition of phosphorus fertiliser did not significantly affect all observation variables in this study. The addition of zeolite fertiliser showed a significant effect on the variable number of leaves, plant fresh weight, and root fresh weight where treatment L2 (90 g/polybag) showed the highest effect.